Role of Resilience Factors Affecting Work Performance among Allied Health Professionals: A Systematic Review - H Lalrohlui; Jyoti Sharma; Mohammad Sidiq; Aksh Chahal (Journal of Clinical and Diagnostic Research, 2025)
Introduction: It is becoming more and more important for health services worldwide that allied health professionals make sure they give patients the most appropriate and timely care. However, the demands of time pressure, workload, emotional worries, and interacting with numerous professional groups and clients frequently cause allied health practitioners stress that is detrimental to their physical and mental wellbeing. To cope with daily high-performance resilience, play an important role where resilience is defined as a capacity to bounce back from or change with ease. Aim: The study aimed to to identify the resilience elements that have an impact on work performance of allied health professionals. Materials and Methods: In the present Systematic review electronic databases like Scopus, PubMed, Google Scholar, Cochrane and Pedro were searched with keyword “allied health professionals”, “resilience factors”, “resilience” and “performance’’ using boolean operators “AND” and “OR” in between (“Resilience” OR “Resilience factors” OR “Psychological resilience” OR “Occupational resilience” OR “Coping strategies”) AND (“Allied Health Professionals” OR “Health workers” OR “Rehabilitation professionals” OR “Physiotherapists” OR “Occupational therapists” OR “Speech-language pathologists” OR “Radiographers” OR “Medical technologists”) AND (“Work performance” OR “Job performance” OR “Occupational performance” OR “Work productivity” OR “Job satisfaction” OR “Professional efficacy” OR “Burnout” OR “Stress management”).A total of 291 articles were found in the year between January 2013 to December 2023. A number of 63 articles fell under eligibility criteria out of which 14 were included in this review. Results: The resilience factors affecting work performance of allied health professionals were found from the literature. Primary resilience factors like coping, communication, mindfulness, and self-efficacy directly enhance work performance by improving stress management, focus, and confidence. Secondary factors such as positive emotions, self-management, and grit support sustained productivity and perseverance. Tertiary factors including life experience, maturity, optimism, social support, and healthy habits indirectly strengthen resilience, promoting well-being and long-term effectiveness. Together, these factors build a foundation for consistent, high-level work performance in challenging environments. Conclusion: The study concluded key factors that impact the performance of allied health professionals were effective ways of coping, good communication skills, practicing mindfulness and feeling confident in one’s abilities.